(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Asthma and COPD are the respiratory diseases. Asthma is a persistent lung disease presented with chronic cough, SOB that occurs from bronchial hyper responsiveness and inflammation. COPD is also known as COAD (Chronic obstructive airway disease) is the airway obstructive disease which leads to obstruction of the airflow that is either partially or completely and results in dysfunction of the lungs disease. The purpose of the study is to provide the clinical pharmacist assisted counselling towards usage of inhaler devices and assessing its impact by using inhaler specific checklist for both MDI,DPI and nebulizer assessment. Inhaler devices such as nebulizer, metered dose inhaler (MDI), dry powder inhaler(DPI) have an advantageous impact in control of asthma and COPD. Materials and Methods: A prospective interventional study was held for half of the year. All the data were collected, documented and analyzed based on standard protocol. The collected data were statistically analysed by using paired T –test. Results: In this study we observed that patients had improved the correct usage of inhaler devices after counselling than before and also helps to relieve from symptoms. Conclusion: We conclude that patients had improved their performance on usage of inhaler devices in post counselling than to pre counselling. The involvement of clinical pharmacist in counselling shows improvement on correct usage of inhalation technique in COPD and asthma patients.